Determination of the change in the structural performance of an RC building due to a nearby deep excavation. (March 2023) - Mangir, Atakan; Cosgun, Turgay; Sayin, Baris; Okumus, Vefa; Gunes, Baris
Abstract: In this study, the structural performance of an existing thirteen-story reinforced concrete building is evaluated and compared to the case caused by the ground motion due to a nearby deep excavation. Accordingly, the effects of this event on structural safety emerge. First of all, the structural system details, geometry, layout, and material properties of the existing building are determined by field surveys and laboratory studies. Secondly, the structure is modelled with finite element software, and nonlinear structural analyses are carried out with pushover analyses, taking into account various loading conditions, which consist of four cases: vertical and seismic loading with and without ground displacements caused by the event. The nonlinear behaviour is defined, and deformation values in the cross-sections of the structural elements are obtained by using fiber hinges in vertical structural elements and lumped hinges on the beams. Finally, the seismic performance levels of the building are found before and after excavation, taking into account the latest Turkish Building Earthquake Code (TBEC 2018). This case study provides a methodology for engineering practice in evaluating the structural performance and modelling of reinforced concrete (RC) buildings affected by a similar deep excavation event.